Assessment Of Awareness Level and Perception In Usage Of Plastic Bags And Its Hazards Among Secondary School Students - Mohi Ud Din; Zain Arif; Hafiz Usama Naveed; Maryam Tauseef; Nouman Yaseen; Talha Mahboob (Journal of Rawalpindi Medical College)
Objective: The objectives of the study were to determine the frequency of plastic bag usage among secondary school students of Islamabad and to assess their knowledge about plastic bag-associated pollution,  its disposal and legislation.